2012
DOI: 10.3389/fpsyt.2012.00092
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Baseline Marijuana Use on Treatment of Cocaine Dependence: Application of an Informative-Priors Bayesian Approach

Abstract: Background: Marijuana use is prevalent among patients with cocaine dependence and often non-exclusionary in clinical trials of potential cocaine medications. The dual-focus of this study was to (1) examine the moderating effect of baseline marijuana use on response to treatment with levodopa/carbidopa for cocaine dependence; and (2) apply an informative-priors, Bayesian approach for estimating the probability of a subgroup-by-treatment interaction effect. Method: A secondary data analysis of two previously pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although these methods have many benefits, they often heavily rely on p ‐values, which are typically misinterpreted and do not provide information about the magnitude of a treatment effect, which is important when determining potential clinical efficacy of a drug (Wijeysundera et al, 2009). Alternative statistical methods, such as Bayesian statistical inference, may provide additional benefits to analysis of self‐administration studies, such as directly addressing the alternative hypothesis, rather than indirectly rejecting the null hypothesis (Green et al, 2012). Bayesian statistical inference has been effectively used in clinical trials (see Green et al, 2012; Wijeysundera et al, 2009) and have been recommended to be used in conjunction with typical inferential statistical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these methods have many benefits, they often heavily rely on p ‐values, which are typically misinterpreted and do not provide information about the magnitude of a treatment effect, which is important when determining potential clinical efficacy of a drug (Wijeysundera et al, 2009). Alternative statistical methods, such as Bayesian statistical inference, may provide additional benefits to analysis of self‐administration studies, such as directly addressing the alternative hypothesis, rather than indirectly rejecting the null hypothesis (Green et al, 2012). Bayesian statistical inference has been effectively used in clinical trials (see Green et al, 2012; Wijeysundera et al, 2009) and have been recommended to be used in conjunction with typical inferential statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative statistical methods, such as Bayesian statistical inference, may provide additional benefits to analysis of self‐administration studies, such as directly addressing the alternative hypothesis, rather than indirectly rejecting the null hypothesis (Green et al, 2012). Bayesian statistical inference has been effectively used in clinical trials (see Green et al, 2012; Wijeysundera et al, 2009) and have been recommended to be used in conjunction with typical inferential statistical methods. Future cocaine self‐administration research may benefit from the use of Bayesian statistical inference in addition to other common analyses in self‐administration research, as these methods can detect subtle differences in effects with smaller sample sizes (Lee & Song, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggest that cannabis use either before entering or after being discharged from treatment may be associated with adverse treatment outcomes among opioid and cocaine-dependent patients [ 38 , 39 , 40 ]. For example, a prospective study of heroin-abstinent patients found that cannabis use was a significant predictor of heroin use resumption [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a prospective study of heroin-abstinent patients found that cannabis use was a significant predictor of heroin use resumption [ 40 ]. A secondary analysis of two completed clinical trials of treatment for cocaine dependence found an effect of baseline marijuana use on response to treatment for cocaine dependence; specifically, more days of marijuana use at baseline predicted lower treatment effectiveness (cocaine-negative urines) among those receiving levodopa/carbidopa, but not in the placebo condition [ 39 ]. The authors speculated that higher baseline marijuana use may be a proxy for cocaine severity.…”
Section: Introductionmentioning
confidence: 99%